ANALISIS GEOTEKNIK DAN DINAMIK STRUKTUR UNTUK PERKUATAN ABUTMEN JEMBATAN WAY PAGAR ALAM YANG LONGSOR - Aminudin Syah; Fikri Alami; Ofik Taupik Purwadi; Endro Prasetyo Wahono (UNIB Press, 2025)
The Way Pagar Alam Bridge in Tanggamus Regency experienced failure at one of its widened abutments due to a combination of weak geotechnical conditions, rainfall infiltration, and riverbank erosion. This study aims to assess the structural and geotechnical conditions of the bridge and develop an effective reinforcement design. The methodology includes visual inspection, laboratory testing of soil, structural vibration monitoring, and slope stability analysis using limit equilibrium-based software. Vibration tests indicate that the bridge superstructure remains stiff, with vertical deflection well below the allowable limit. Subsurface investigations revealed the presence of expansive clay with low bearing capacity in shallow layers. Stability analysis shows that a combined reinforcement system—comprising a retaining wall, gabion protection, and mini piles—can enhance the slope safety factor to 1.99 (static) and 1.73 (dynamic), meeting applicable engineering standards. The proposed design is considered effective and applicable for bridge rehabilitation in tropical regions with soft subgrade conditions.